Evaluation of Yield and Physicochemical Quality of Pentadesma butyracea Butter Obtained by Different Traditional Extraction Methods in Ghana - Josephine Akuba Timtey; Francis Alemawor; William Otoo Ellis; Jacob K. Agbenorhevi; Nana Baah Pepra-Ameyaw (International Journal of Food Science)
Pentadesma butyracea seed butter or fat (PBSB) is a vegetable fat extracted from the seeds of the P. butyracea plant. The butter has potential use in the food, pharmaceutical, and cosmetic industries. The study investigated traditional PBSB processing methods in Ghana and evaluated their effects on yield, physicochemical parameters, and fatty acid composition. Four traditional extraction methods were identified and evaluated, and these methods are direct wet extraction of PBSB from a fresh mixture of the seed paste and water (DEW); wet extraction of PBSB from a 12-hour fermented mixture of the seed paste and water (FWO); direct wet extraction of PBSB from a fresh mixture of the seed paste, salt, and water (DES); and wet extraction of PBSB from a 12-hour fermented mixture of the seed paste, salt, and water (FSO). Results of physicochemical properties of the PBSB samples showed moisture content of 0.06-0.07%, free fatty acid of 1.38-2.43%, iodine value of 56.50-56.85 Wijs, peroxide value of 5.58-8.52 mEq/kg, relative density of 0.91, refractive index of 1.462-1.464, percent impurities of 0.015-0.017%, saponification value of 165.57-178.02 mg KOH/g, and percent unsaponifiable matter of 2.60-3.18%. The PBSB yield varied in the range of 21.68-26.97%, with the highest average butter yield observed for FWO. Seventeen fatty acids were characterized in the PBSB samples, and they included ten saturated fatty acids, five monounsaturated fatty acids, and two polyunsaturated fatty acids. Key fatty acids found in the PBSB samples were oleic acid (51.21-51.31%), stearic acid (43.22-43.33%), palmitic acid (2.91-3.07%), linoleic acid (0.49-0.51%), linolenic acid (0.12-0.20%), and arachidic acid (0.14-0.15%). PBSB samples produced by the various traditional extraction methods in Ghana recorded similar physicochemical characteristics as unrefined shea butter per the Regional Standard for Unrefined Shea Butter (CXS 325R-2017) as well as Cook Brand Margarine, a common commercial baking fat, and thus, their potential food application such as an alternative shortening/ingredient could be explored in a future study.